PERSPEKTIF OPERA BATAK SISINGAMANGARAJA XII EPISODE BORU LOPIAN ULUPORANG TANO BATAK - Rosta Minawati; Enrico Alamo; Sherli Novalinda; Sulaiman Juned (Gorga : Jurnal Seni Rupa, 2022)
This creation research formulates the struggle of Boru Lopian son of Sisingamangaraja XII against Dutch colonialism. In addition to seeing as the figure of the son of King Sisingamangaraja XII, the research is also directed at the story of Boru Lopian who is famous for his courage when dealing with the invaders. Even though he comes from an honorable lineage, Boru Lopian is never arrogant and arrogant. Unfortunately, this humanist figure also died in the guerrilla against the Dutch colonialists. The final result of the research is a Batak opera performance with the title, Sisingamangaraja XII episode Boru Lopian, Uluporang Tano Batak. The process of performing Batak opera begins with the creation of a Batak opera script obtained based on research on Boru Lopian. Then packed with some elements of modern theater without leaving the inherent traditional values. This combination was deliberately chosen as part of the stages towards the novelty of the arable concept (innovation). The research method of creation is done through observation, research and interviews with community leaders. The arrangement of the story of the Batak opera Sisingamangaraja XII episode of Boru Lopian, Uluporang Tano Batak is a reorganization of a history. Which of course undergoes several changes, from the actual story to a story that is 'spiced up' with the present context. This is done in order to become familiar with the audience. The authenticity of traditional Batak opera forms is combined with artistic elements of modern theater so that the atmosphere and setting of the event becomes contextual. The goal is to facilitate the presence of building elements, artifacts, past events that are impossible to present simultaneously on the current stage. The structure in the Batak opera Sisingamangaraja XII episode Boru Lopian, Uluporang Tano Batak has similarities with the two previous Batak opera performances. Because it was designed for three opera performances of Batak Sisingamangaraja XII.Keywords: Boru Lopian, perspective, opera Batak. AbstrakPenelitian penciptaan ini merumuskan perjuangan Boru Lopian anak Sisingamangaraja XII dalam melawan penjajahan Belanda. Selain melihat sebagai sosok anak Raja Sisingamangaraja XII, penelitian juga diarahkan pada kisah Boru Lopian yang terkenal akan keberaniaannya saat berhadapan dengan para penjajah. Walaupun berasal dari keturunan terhormat, Boru Lopian tidak pernah sombong dan tinggi hati. Sayangnya sosok yang humanis ini turut tewas dalam gerilya melawan penjajah Belanda. Hasil akhir dari penelitian adalah, pertunjukan opera Batak dengan judul, Sisingamangaraja XII episode Boru Lopian, Uluporang Tano Batak. Proses pertunjukan opera Batak didiawali dengan pembuatan naskah opera Batak yang didapatkan berdasarkan riset tentang Boru Lopian. Kemudian dikemas dengan beberapa unsur-unsur teater modern tanpa meninggalkan nilai-nilai tradisi yang melekat. Perpaduan ini sengaja dipilih sebagai bagian dari tahapan menuju kebaruan dari konsep garapan (inovasi). Metode penelitian penciptaan dilakukan melalui observasi, riset dan wawancara dengan tokoh masyarakat. Penataan cerita opera Batak Sisingamangaraja XII episode Boru Lopian, Uluporang Tano Batak ini merupakan penataan ulang sebuah sejarah. Yang didalamnya tentunya mengalami beberapa perubahan, dari cerita yang sebenarnya menjadi cerita yang ‘dibumbui’ dengan konteks kekinian. Hal ini dilakukan agar menjadi akrab dengan penonton. Keaslian bentuk opera Batak tradisi dipadukan dengan elemen-elemen artistik teater modern agar suasana dan latar peristiwa menjadi kontekstual. Tujuannya untuk mempermudah hadirnya unsur bangunan, artefak, peristiwa masa lalu yang tidak mungkin dihadirkan secara bersamaan diatas panggung saat ini. Struktur dalam opera Batak Sisingamangaraja XII episode Boru Lopian, Uluporang Tano Batak memiliki kesamaan dengan dua pertunjukan opera Batak sebelumnya. Karena dirancang untuk tiga pertunjukan opera Batak Sisingamangaraja XII.Kata Kunci: Boru Lopian, perspektif, opera Batak. Authors: Rosta Minawati : Institut Seni Indonesia PadangpanjangEnrico Alamo : Institut Seni Indonesia PadangpanjangSherli Novalinda : Institut Seni Indonesia PadangpanjangSulaiman Juned : Institut Seni Indonesia Padangpanjang References: Alamo, E., Eliza,M., Syailillah, G. (2020). Makna dan Fungsi Ulos Pada Pusat Latihan Opera Batak (PLOt) Pematang Siantar Di Pematang Siantar Sumatera Utara. Gorga: Jurnal Seni Rupa, 10(1), 94. https://doi.org/10.24114/gr.v10i1.24824Alamo, E., Minawati, R., Sulaiman, S., & Novalinda, S. (2020). Opera Batak Sisingamangaraja XII Episode Ugamo Malim Horja Bolon Na Parpudi: Usungan Tradisi dan Kontemporer. Dance and Theatre Review. Jurnal Tari, Teater, dan Wayang, 3(2), 59.Alamo, E.,(2014). Sampuraga Penciptaan Opera Batak. Ekspresi Seni: Jurnal Pengetahuan dan Seni, 16(1),1.Guntur. (2016). Metode Penelitian Artistik. Surakarta: ISI Press.Hariwijaya, M. (2007). Metodologi dan Tehnik Penulisan Skripsi, Tesis, dan Disertasi. Jakarta: Elmatera Publishing.Joel, M. Charon. Eighth Edition (2012) Ten Questions: A Sociological Perspective. USA: Cengage Learning.Moleong, Lexy J. (2000). Metodologi Penelitian  Kualitatif. Bandung: Remaja Rosdakarya.Martono, Nanang. (2012) Sosiologi Perubahan Sosial: Perspektif Klasik, Modern, Posmodern, dan Poskolonial. Jakarta: Raja Grafindo Persada.Pavis, Patrice. (1990). Theatre at The Crossroad of Culture. London and New York: Transl. Loren Kruger.Purba, Krismus. (2010). Opera Batak Tilhang Serindo: Pengikat Budaya Masyarakat Batak Toba di Jakarta.Yogyakarta: Kalika Bantul.Sulaiman, S., Minawati, R., Alamo, E., & Novalinda, S. (2019). Analisis Struktur Pertunjukan Opera Batak Sisingamangaraja XII: Episode Tongtang I Tano Batak. Panggung Bandung: Jurnal Seni Budaya, 29(2),160.Sumaatmadja dan Winardit. (1999). Perspektif Global. Jakarta: UT.Sutopo, H.B. (2006). Metodologi Penelitian Kualitatif Dasar Teori dan Terapannya dalam Penelitian. Surakarta: UNS Press.Yudiaryani. (2002). Panggung Teater Dunia, Perkembangan dan PerubahanKonvensi Seni Teater. Yogyakarta: Pustaka Gondo Suli.